Green attitude and purchase intention towards environmental friendly product / Phuah Kit Teng ... [et al.] - Phuah, Kit Teng; Mun, Waei Ow; Sandhu, Sukjeet Kaur; Kassim, Umi Kalsom (Universiti Teknologi MARA Selangor, 2018)
In this modern era, societal marketing business ethics and corporate social responsibility has become the guideline for green marketing strategies and practices. Consumer concerns towards the environment are the evidence which steadily increases the ecologically conscious marketplace. Consumers' awareness and attitude on food products which market in green marketing is important in guiding their purchasing intention of environmental friendly food products. The purpose of this research is to determine the moderation of consumer attitude on the relationship of subjective norms and perceived behavioral control and consumer purchase intention towards environmental friendly food products. Simple random sampling was used in this study and 151 respondents were interviewed using structured questionnaires. Descriptive analysis, reliability test and hierarchical multiple regression were used to accomplish the objective of this study. The results indicate that there is evidence to conclude that the consumer attitude is moderator in the relationship between subjective norms and their intention to purchase environmental friendly food products. However, attitude is not a moderator variable in the relationship between perceived behaviour control and consumer intention to purchase environmental friendly food products.